Nursing documentation and its relationship with perceived nursing workload: Cross Sectional Study - Hadi, Irwan; Apriani, Baiq Nurainun (Jurnal Ilmiah STIKES Yarsi Mataram, 2023)
Documenting is a central element in accounting for the performance of the nursing profession after making a direct nursing intervention to the client. Data at the hospital shows that the nursing documentation form that has been prepared is incomplete or not filled in completely. Nurses do more non-nursing work and delegates from other health teams. Workload is one of the factors related to the completeness of nursing care documentation. The research method used is a descriptive method of correlation with a cross sectional approach. The number of samples in this study was 56 people with the purposive sampling method. Data analysis using the Spearman Rank statistical test in the SPSS 21 application. The results of this study showed that most nurses' workload was in the moderate category (37.5%) and the documentation of nursing care was that most nurses did incomplete documentation (67.9), while the Spearman Rank test results showed a significance value of 0.011 (P<0.05), which showed there was a relationship between nurse workload and nursing care documentation. Nurses are required to do complete documentation of care because records of all actions given to patients can be used as evidence that nursing care has been carried out correctly, appropriately, and comprehensively.